Studier av cirrusskyer sett fra satellitt i relasjon til flytrafikk - Bork, Jakob (2007)
Abstract On a sunny, cloudless day we often recognize condensation trails (contrails) behind jet aircrafts as narrow, white stripes. Contrails form as a mixture of warm, humid exhaust gases and colder, drier air exceeds water saturation in the plume. The exhaust particles may allow ice nucleation at lower supersaturations than those required under natural conditions. If the relative humidity with respect to ice is higher than 100%, then contrails may persist and evovlve into high-level cirrus clouds. The anthropogenic cirrus clouds have the potential for affecting climate via radiative forcing. Because of the rising global air traffic over the past decades and its associated contrails, there have been a substantial focus on estimates of radiative forcing from contrails compared to the total anthropogenic radiative forcing. In this study we use daily data rather than montly means in comparison to previous studies. The daily data consists of three different datasets taken for one week during summer. For predicting the environmental conditions required for contrail formation and peristence, we have used the Schmidt-Appleman criterion. Correlations will be spatially executed for different cirrus parameters before and after filtering out air traffic, globally and for four high-density air traffic areas. Results from the Schmidt-Appleman criterion indicate best conditions for contrail formation over East-Asia, and parts of Central-Europe and the North-Atlantic flight corridor. But the overall correlations shows a weak agreement between cirrus cloudiness and air traffic density, and even negative for some geographical locations. Best agreement is located over most of Asia, where the summer monsoon is responsible for the high cirrus occurence over this area. In addition, these contrails can persist and consequently affect the Earth’s radiative balance. Reanalysis from ECMWF (European Center for Medium-Range Weather Forecasts) shows that the satellite observations of cirrus can be partly explained by the weather ...